Mental Fatigue, Sleep and Student Success: Psychological Predictors of Academic Performance in Higher Education - Namra Shahzadi; Misbah Arshad; Sarah Mufti (Research Journal of Psychology, 2025)
The current study examined mental fatigue and lack of sleep symptoms as psychological indicators of academic achievement among Pakistani university students. Convenience sampling was used to select 800 students (320 males and 480 females) aged 18 to 25 from various disciplines at the University of Gujarat. Participants completed the Mental Fatigue Scale (Johansson & Rönnbäck, 2014) and the Insomnia Severity Index (Bastien et al., 2001), and academic performance was measured using self-reported GPA from the most recent semester. Statistical studies, including Pearson correlations and multiple linear regression, demonstrated that both mental tiredness (β = -0.41, p <.001) and insomnia severity (β = -0.36, p < 0.001) substantially predicted lower academic achievement. These covariates explained 29% of GPA variance (R² = 0.29, F(2, 797) = 162.84, p <.001). Mental exhaustion and sleeplessness were found to have a high positive connection (r =.52, p <.001), suggesting a similar impact on cognitive and academic performance. These findings underscore the urgent need for comprehensive psychological wellness programs focusing on sleep health and fatigue management to enhance student achievement in Pakistan’s higher education settings.